Development of Education Pancasila Citizenship Learning Media based on Edutainment as an Effort to Nurture the Character of Students of SDN 105343 Ramunia I/II - Anwar Anwar; Eka Nurbulan; Emi Juwita Saragih; Sri Yunita; Yakobus Ndona (Universitas Muhammadiyah Enrekang, 2024)
In this very modern era, it is possible that Indonesian children, especially students, prefer more modern things, so that in learning there are many media that can be used to attract students' interest in learning so that it becomes more interesting. motivated in learning. Pancasila Citizenship Education is the subject that students are least interested in, there are very few people interested in it, therefore edutainment-based interactive media in learning Pancasila Citizenship Education can be useful in attracting students' attention to learning Pancasila Citizenship Education. The media used can make students have a high level of interest and curiosity so that students become more active, creative and have a higher enthusiasm for learning.